QUALITY RELATIONSHIP OF NURSING SERVICES WITH THE LEVEL OF TREATMENT PATIENT SATISFACTION STAY IN PAUH KAMBAR HEALTH CENTER IN PADANG PARIAMAN REGENCY - Eliza, Eliza; Nelli, Septa (Jurnal Kesehatan Saintika Meditory, 2023)
Nurse services are the spearhead in achieving the quality of health services because it is nurses who often have direct contact with patients. The purpose of the study was to determine the relationship between the quality of nursing services with the level of patient satisfaction at the Pauh Kamba Health Center.The research method is analytic survey with cross sectional approach. The study was conducted at the Pauh Kamba Community Health Center, in August - September 2022. The population in this study were all 30 patients treated and the sampling technique used was total sampling. Data collection using a questionnaire with guided interviews, with 30 respondents. The results showed (53.3%) respondents were dissatisfied, and 16 (53.3%) stated that they were not qualified in the service of nurses at the 2023 Pauh Kamba Health Center. After conducting statistical tests there is a significant relationship between quality and level of satisfaction (p value = 0.000) with patient satisfaction.Thus it is necessary to improve the quality of nursing services at the Pauh Kamba Health Center, which can be done by completing the facilities for patients and existing nursing equipment. Also provides training to nurses on the quality of nursing services and plenary services.Abstract should be written briefly and factually. Abstract contains of the clear elaboration of research purpose, result and conclusion. Abstract should be written separately from the article. Reference should not be written in abstract, but if it is indispensable, authors’ name and publication year should be cited. Non standard abbreviation should be avoided, but if it is indispensable, the full name should be specified in its initial mention. The word length is not more than 200 words, written in English. Keywords : Quality, Service, Nursing, Health Center